Pengaruh Edukasi terhadap Pengetahuan Masyarkat Tentang Deteksi Dini Alzheimer di Kelurahan Labuh Baru Pekanbaru - Angga Arfina (STIKes Payung Negeri Pekanbaru, 2021)
Alzheimer's disease is an irreversible brain disorder that causes memory impairment, thinking skills and behavioral changes. Early detection and diagnosis of Alzheimer's disease will provide benefits that help individuals and families of sufferers. Education plays a role in helping the community to increase knowledge about early detection of Alzheimer's disease. This study aims to determine the effect of education on public knowledge about early detection of Alzheimer's in Labuh Baru Village, Pekanbaru City. This research is a quantitative descriptive study with a quasi-experimental pre and post test design without control. The sample of this research is 30 people with consecutive sampling technique. Data was collected using a knowledge questionnaire on Alzheimer's early detection. Data were analyzed using dependent T test statistics. The results showed that there was an increase in knowledge of early detection of Alzheimer's, from an average of 5,733 before education to 6,633 after being given education. The results of the T-test obtained a mean value of 0.900 with a standard deviation of 1.241 and a p value of 0.000, meaning that there is a significant difference in public knowledge about early detection of Alzheimer's between before and after giving education. Education can increase public knowledge about early detection of Alzheimer's disease and more effectively is expected to be able to prevent complications that can arise.